New insight into the flocculation behavior of hydrophilic silica in styrene butadiene rubber composites. Issue 111 (26th October 2015) - Su, Juqiao; Yang, Qi; Tang, Dahang; Huang, Yajiang; Zhao, Zhongguo; Liao, Xia
Abstract : We propose that modified silica filled rubber composites with moderate silica flocculation possesses preferable resistance to crack growth by the crack tip deflection mechanism. Abstract : The flocculation behavior of hydrophilic silica in styrene butadiene rubber composites has been carefully analyzed by rheology methodology. An evident increment of the elastic modulus ( G ′) can be observed over a critical temperature for unmodified composites due to a significant filler network composed of loose silica clusters, while the increment of G ′ for modified composites is slight. Still, the flocculation behavior is confirmed by nonlinear dynamical strain sweeps and Atomic Force Microscopy (AFM). Thereafter, modified and unmodified silica filled composites, with varied processing temperature, are vulcanized respectively, and corresponding fatigue crack growth tests are implemented. A modified composite with a processing temperature of 130 °C possesses the smallest exponent law, b, and d c /d n at a given tearing energy ( T ). We deduce that fatigue crack growth changes from a local stress concentration mechanism originating from severe silica flocculation within unmodified composites to a crack deflection growth mechanism originating from moderate silica flocculation within modified composites. Based on the crack tip morphology investigations at T = 5, 10, 15, 20 kJ m −2, it can be proposed that the crack tip morphology has a tear energy dependence, closely related to the flocculation behavior of silica.